2020
DOI: 10.1371/journal.pone.0234903
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of a social caterpillar, Drepana arcuata: De novo assembly, functional annotation and developmental analysis

Abstract: The masked birch caterpillar, Drepana arcuata, provides an excellent opportunity to study mechanisms mediating developmental changes in social behaviour. Larvae transition from being social to solitary during the 3 rd instar, concomitant with shifts in their use of acoustic communication. In this study we characterize the transcriptome of D. arcuata to initiate sociogenomic research of this lepidopteran insect. We assembled and annotated the combined larval transcriptome of "social" early and "solitary" late i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…The overall contig number was similar to values reported in other lepidopteran transcriptome studies, such as Pieris rapae [53] and Plutella xylostella [54]. We identified ORFs for~22% of the contigs, which is comparable to the proportion assigned in other studies [55][56][57], although some authors have reported higher annotation rates [58]. In this context, we note that~25% of the assembled contigs were too short for ORF prediction (≤300 bp), probably including small and non-coding RNAs and rRNA fragments left over from rRNA depletion.…”
Section: Discussionsupporting
confidence: 87%
“…The overall contig number was similar to values reported in other lepidopteran transcriptome studies, such as Pieris rapae [53] and Plutella xylostella [54]. We identified ORFs for~22% of the contigs, which is comparable to the proportion assigned in other studies [55][56][57], although some authors have reported higher annotation rates [58]. In this context, we note that~25% of the assembled contigs were too short for ORF prediction (≤300 bp), probably including small and non-coding RNAs and rRNA fragments left over from rRNA depletion.…”
Section: Discussionsupporting
confidence: 87%
“…Isoforms of the octopamine receptor gene were previously found to be upregulated in socially grouping early instars of D. arcuata relative to solitary late instars [ 7 ]. After aligning the octopamine gene isoforms using Clustal Omega ( https://www.ebi.ac.uk/Tools/msa/clustalo/ ), conserved regions were used for siRNA design using Dharmacon’s siDESIGN tool ( https://horizondiscovery.com/en/products/tools/siDESIGN-Center ).…”
Section: Methodsmentioning
confidence: 99%
“…First, during development these larvae predictably transition from living socially to solitarily, with the 3rd instar as the transition stage [ 6 ]. Second, a transcriptomic comparison between social and solitary phenotypes of D. arcuata showed differential expression of a number of genes associated with sociality in other organisms [ 7 ]. Among these, octopamine receptor (OAR) is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw reads, without any trimming (as suggested by the assembler), were then used for hybrid genome assembly using MaSuRCA v3.3.1 assembler [7] with the default parameters. De novo assemblies generated using MaSuRCA were further optimized for contiguity by using AGOUTI v0.3.3 (Annotated Genome Optimization Using Transcriptome Information) [8] using RNA-sequencing data from NCBI Bioproject PRJNA556910 [9] . The completeness of assembly was evaluated using BUSCO v3.0 ( https://busco.ezlab.org ) against the Arthropoda database (Arthropoda_Odb9).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%